2018
DOI: 10.1002/oby.22195
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Mice Overeat High‐Fat Diets? How High‐Fat Diet Alters the Regulation of Daily Caloric Intake in Mice

Abstract: ObjectiveAd libitum high fat diet (HFD) spontaneously increases caloric intake in rodents, which correlates positively with weight gain. However, it remains unclear why rodents overeat HFD. We investigated how changing the proportion of diet that came from HFD might alter daily caloric intake in mice.MethodsMice were given 25%, 50%, or 90% of their daily caloric need from HFD, along with ad libitum access to a low-fat rodent chow diet. Food intake was measured daily to determine how these HFD supplements impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 44 publications
4
46
1
1
Order By: Relevance
“…In rodents, ad libitum access to HFD increases the daily caloric intake, and leads to weight gain [68]. While an HFD is capable of invoking mechanisms that limit total daily caloric intake, C57BL/6 mice over-consume an HFD when provided ad libitum [13]. We found that male Tac:SW mice developed obesity on the HFD; however, unlike male C57BL/6 mice, CV male Tac:SW mice reduced their feed intake on an HFD, suggesting a strain difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, ad libitum access to HFD increases the daily caloric intake, and leads to weight gain [68]. While an HFD is capable of invoking mechanisms that limit total daily caloric intake, C57BL/6 mice over-consume an HFD when provided ad libitum [13]. We found that male Tac:SW mice developed obesity on the HFD; however, unlike male C57BL/6 mice, CV male Tac:SW mice reduced their feed intake on an HFD, suggesting a strain difference.…”
Section: Discussionmentioning
confidence: 99%
“…These diets are rich in simple digestible sugars, saturated lipids, or both, and possess a high fractional feed conversion. Moreover, when fed these diets, mice do not sufficiently decrease feed consumption to maintain their caloric energy balance [13]. In mice, abdominal obesity, insulin resistance, and other indicators of MetS develop with DIO [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In general, HFD feeding in rodents is associated with an increase in food consumption and obesity (Lutz and Woods 2012). Unit now, the mechanism for hyperphagia (over-eating) and subsequent weight gain in HFD-fed animal models and humans remains a matter of debate (Licholai et al 2018). However, currently available data suggest that such effect is due to multiple mechanisms including homeostatic (endocrine and neural), hedonic (palatability), and cognitive feedback (Hall et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, currently available data suggest that such effect is due to multiple mechanisms including homeostatic (endocrine and neural), hedonic (palatability), and cognitive feedback (Hall et al 2014). Upto-date, it is well-accepted that dysregulation of the endocrine-hippocampus axis (such as leptin resistance), as well as dysregulation of many brain receptors such as melanocortin 4 receptors (MC4R), is the major mechanisms by which HFD-stimulates over-feeding and obesity (Farooqi and Leptin 2009;Friedman, 2009Licholai et al 2018. Besides, HFD is associated with altered liver lipid metabolism due to dysregulation of numerous fatty acid and cholesterol synthesis and fatty acid oxidation pathways, which ultimately leads to over-synthesis of TGs, TC, and LDL, hyperlipidemia, mitochondria, damage, oxidative stress, hyperglycemia, insulin resistance, fatty liver, and hepatic damage and cirrhosis (Wilkes et al 1998;Kakimoto and Kowaltowski 2016;Jin et al 2017;Khaleel et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The authors investigated the weight gain was associated with increases energy intake. The authors also found that different fat source does no significant effect on caloric intake, but mice over-ate on diet with higher total fat (Licholai et al, 2018).…”
Section: Discussionmentioning
confidence: 91%